The investment casting process of optimization / Md. Khairul Fadli Mestor, Khir Johari Ismail and Mohd Fahmi Hasan - Mestor, Md. Khairul Fadli; Ismail, Khir Johari; Hasan, Mohd Fahmi (2005)
A process is described for permanently closing internal and surface casting defect, such as shrinkage and hot tears, within high temperature superallovs. The process imolves the simulation application of temperature and pressure using a hot- lsostatic pressure (HIP) autoclaves. When applied to investment casting the process significantly improves in other structural characteristic are discussed along with potential limitations in the process. The purpose of this experiment is to provide more effective and quality of product. This is only the experiment we take in action for using a bit little material for maximum cost. We use all equipment machines for using investment casting process. This process is take lime to be done